Differential Effects of Insulin-Like Growth Factor Binding Protein-6 (IGFBP-6) on Migration of Two Ovarian Cancer Cell Lines - Yang, Zhiyong; Bach, Leon A. (Frontiers in Endocrinology, 2015)
IGFBP-6 inhibits angiogenesis as well as proliferation and survival of rhabdomyosarcoma cells. However, it promotes migration of these cells in an IGF-independent manner. The IGF system is implicated in ovarian cancer, so we studied the effects of IGFBP-6 in ovarian cancer cells. Methods: The effects of wild type (wt) and a non-IGF-binding mutant (m) of IGFBP-6 on migration of HEY and SKOV-3 ovarian cancer cells, which respectively represent aggressive and transitional cancers, were studied. ERK and JNK phosphorylation were measured by Western blotting. Results: IGF-II, wt- and mIGFBP-6 each promoted SKOV3 cell migration by 77-98% (p<0.01). In contrast, IGF-II also increased HEY cell migration to 155 ± 13% of control (p<0.001), but wtIGFBP-6 and mIGFBP-6 decreased migration to 62 ± 5% and 66 ± 3% respectively (p<0.001). In these cells, coincubation of IGF-II with wt but not mIGFBP-6 increased migration. MAP kinase pathways are involved in IGFBP-6-induced rhabdomyosarcoma cell migration, so activation of these pathways in HEY and SKOV3 cells was studied. wt and mIGFBP-6 increased ERK phosphorylation by 62-99% in both cell lines (p<0.05). wtIGFBP-6 also increased JNK phosphorylation by 139-153% in both cell lines (p<0.05), but the effect of mIGFBP-6 was less clear. ERK and JNK inhibitors partially inhibited the migratory effects of wt and mIGFBP-6 in SKOV3 cells, whereas the ERK inhibitor partially restored wt and mIGFBP-6-induced inhibition of HEY cell migration. The JNK inhibitor had a lesser effect on the actions of wtIGFBP-6 and no effect on the actions of mIGFBP-6 in HEY cells. Conclusions: IGFBP-6 has opposing effects on migration of HEY and SKOV3 ovarian cancer cells, but activates MAP kinase pathways in both. Delineating the pathways underlying the differential effects on migration will increase our understanding of ovarian cancer metastasis and shed new light on the IGF-independent effects of IGFBP-6.